Termična obdelava nerjavnega jekla za gradnjo UVV sistemov - Nemanič, Vincenc (Kovine zlitine tehnologije, 1998)
Stainless steel with its unique mechanical properties is the most frequently used material for manufacturing chambers and components for ultrahigh vacuum (UHV). Its disadvantage is hydrogen outgassing which makes obtaining of UHV troublesome. Vacuum annealing and prolonged in situ bake out are applied methods to reduce the outgassing rate to acceptable level of ?$10^{-12}$?mbar.l/(s.?$cm^2$?). Theory of hydrogen putgassing based for decades on diffusion as limiting mechanism which completely failed when very low outgassing rates were required. Recombination limited outgassing was introduced recently and explains the required duration and temperature of bake out better than just diffusion limited theory. Measured values of recombination rate ?$K_L$? are scattered over orders of magnitude which shows the importance of surface composition and it's structure . The surface of stainless steel is covered with oxides and other deposits which persist normal cleaning procedure. In the paper, outgassing rates are given on the dimensionless scale of previous thermal treatment for reported range of reacombination coefficient ?$K_L$?. Numerical simulations of bake out with different values of D and ?$K_L$? are made in order to predict required procedure to obtain very low outgassing rates. Our diagrams enable to evaluate also the advantage of modern surface treatment methods as a replacement of prolonged vacuum bake out.
Keywords: vakuumska tehnika; razplinjevanje; vodik; prenos snovi